Penerapan Model PBL Berbasis Experiential Learning untuk Meningkatkan Kemampuan Peserta Didik Kelas XII Teknik Kendaraan Ringan - Koto, Rahmat Desman; Purwanto, Wawan; Yuniswar, Yuniswar; Wagino, Wagino (Universitas Negeri Padang, 2025)
This research aims to improve students' ability to dismantle vehicle alarm systems through the implementation of Problem Based Learning (PBL) model based on Experiential Learning in Light Vehicle Engineering class XII. The research method used was Classroom Action Research (CAR) with 3 cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The research subjects were 30 students of class XII Light Vehicle Engineering at SMK Negeri 1 West Sumatra. Data collection was carried out through observation, tests, and documentation. The results showed an increase in students' dismantling ability from cycle I (68.5%), cycle II (75.2%), to cycle III (83.7%). The PBL model based on Experiential Learning effectively improves students' practical skills through direct experience, reflection, conceptualization, and Active Experimentation. This research concludes that the PBL model based on Experiential Learning can be an effective alternative in learning vehicle alarm system dismantling.